Efektifitas Debridemen Mekanik Pada Luka Bakar Derajat III Terhadap Kecepatan Penyembuhan Luka - Nurma Afiani; Sanarto Santoso; Tina Handayani N; M. Fendi Nur Yahya (Jurnal Keperawatan, 2019)
Third degree burn is a special wound cause consist of eschar for a long time. Kept eschar in third degree burn will delay healing procces. That is why eschar should be disapper by debridement process. Mechanical debridement used in this research. The aim of this research is to know the differences between mechanical debridement 24 hour and 48 hour in healing acceleration. This research is a true experimental by using post test only control group design. The samples was selected by simple random sampling and was divided into three groups, each group consist of six rats, they are 24 hour group, 48 hour group and control group. The data was analyzed by one-way ANOVA then followed by Post Hoc LSD. The one way ANOVA result p = 0,018 (p < 0,05) so there was a significant difference between control group and experimental groups. But the Post Hoc LSD results p = 0,123 ( p > 0,05) so there was no significant difference between 24 hour group and 48 hour group in healing acceleration. For further researchers, it is suggested to use microscopic technique to know the effect of mechanical debridement in healing acceleration.